The impact of the traceability of the information systems on humanitarian logistics performance: Case study of Indonesian relief logistics services - Ilyas Masudin; Evan Lau; Nika Tampi Safitri; Dian Palupi Restuputri; Dwi Iryaning Handayani (Cogent Business & Management, 2021)
This article investigates the impact of traceability of the quality of the information system on humanitarian logistics performance. There are four variables studied, namely electronic data interchange (EDI) adoption, blockchain (BC) adoption, radio frequency identification (RFID) adoption, traceability of humanitarian logistics, and humanitarian logistics performance. This research was conducted to assess disaster logistics services in the implementation of service principles in humanitarian logistics. The conceptual model is modeled by introducing three information technologies as independent variables and the humanitarian traceability and logistics performance as dependent variables. The questionnaire was distributed to 96 respondents, and the data was processed using PLS-SEM 2.0. The results show that EDI adoption has no significant effect on the traceability of humanitarian logistics. In contrast, BC and RFID adoption has a significant effect on the traceability of humanitarian logistics. In addition, this study also shows that humanitarian logistics traceability has a significant impact on humanitarian logistics performance.
Keywords: 650; Traceability; technology adoption; EDI; blockchain; RFID; humanitarian logistics